The Ability of Zika virus Intravenous Immunoglobulin to Protect From or Enhance Zika Virus Disease - Pinto, Amelia K.; Hassert, Mariah; Han, Xiaobing; Barker, Douglas; Carnelley, Trevor; Branche, Emilie; Steffen, Tara L.; Stone, E. Taylor; Geerling, Elizabeth; Viramontes, Karla M.; Nykiforuk, Cory; Toth, Derek; et al. (Frontiers in Immunology, 2021)
The closely related flaviviruses, dengue and Zika, cause significant human disease throughout the world. While cross-reactive antibodies have been demonstrated to have the capacity to potentiate disease or mediate protection during flavivirus infection, the mechanisms responsible for this dichotomy are still poorly understood. To understand how the human polyclonal antibody response can protect against, and potentiate the disease in the context of dengue and Zika virus infection we used intravenous hyperimmunoglobulin (IVIG) preparations in a mouse model of the disease. Three IVIGs (ZIKV-IG, Control-Ig and Gamunex) were evaluated for their ability to neutralize and/or enhance Zika, dengue 2 and 3 viruses in vitro. The balance between virus neutralization and enhancement provided by the in vitro neutralization data was used to predict the IVIG concentrations which could protect or enhance Zika, and dengue 2 disease in vivo. Using this approach, we were able to define the unique in vivo dynamics of complex polyclonal antibodies, allowing for both enhancement and protection from flavivirus infection. Our results provide a novel understanding of how polyclonal antibodies interact with viruses with implications for the use of polyclonal antibody therapeutics and the development and evaluation of the next generation flavivirus vaccines.